How Do Surgeon Preferences and Technique Variances Affect Outcome?. Issue 1 (September 2020) - Axiopoulou, Anastasia; Lin, Katherine; Watson, Keith; Cao, Caroline G.L.
Surgeons' training can greatly influence their surgical approach and tool selection. A hierarchical task analysis and time analysis were conducted to compare differences in the use of two different surgical tools in robot-assisted hysterotomy. Hysterectomy is a common surgery performed to remove the uterus, requiring complete visualization of the anatomy field and movement control of the uterus. This manipulation of the uterus can be accomplished by either a uterine manipulator or a myoma screw. Results revealed that even though the surgical tasks and subtasks were similar, the visual presentation of critical anatomy was vastly different. The uterine manipulator with a colpotomizer cup provided clear delineation of the cervicovaginal canal, while allowing easier manipulation of the uterus. The myoma screw provided minimal visual aid, limited manipulation of the uterus, and possibly more bleeding from penetrating the uterus. The uterine manipulator may be a better choice for less experienced surgeons.